2016
DOI: 10.4049/jimmunol.1403104
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 and Carbon Monoxide PromoteBurkholderia pseudomalleiInfection

Abstract: The environmental bacterium and potential biothreat agent Burkholderia pseudomallei causes melioidosis, an often fatal infectious disease. Increased serum bilirubin has been shown to be a negative predictive factor in melioidosis patients. We therefore investigated the role of heme oxygenase-1 (HO-1), which catalyzes the degradation of heme into the bilirubin precursor biliverdin, ferrous iron, and CO during B. pseudomallei infection. We found that infection of murine macrophages induces HO-1 expression, invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 77 publications
7
35
0
Order By: Relevance
“…Interestingly, they found that the knockdown of HMOX1 results in clearance of B. pseudomallei, while the treatment of macrophages with an inducer of HMOX1, CoPPIX, leads to an increased bacterial load. In agreement with these findings, the administration of CORM‐2 to mice infected with B. pseudomallei supports higher bacterial growth in the lungs, liver, and spleen .…”
Section: Bacterial Infectionssupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, they found that the knockdown of HMOX1 results in clearance of B. pseudomallei, while the treatment of macrophages with an inducer of HMOX1, CoPPIX, leads to an increased bacterial load. In agreement with these findings, the administration of CORM‐2 to mice infected with B. pseudomallei supports higher bacterial growth in the lungs, liver, and spleen .…”
Section: Bacterial Infectionssupporting
confidence: 82%
“…Stolt et al,. demonstrated that infection with B. pseudomallei leads to the induction of HMOX1 in RAW264.7 macrophages and murine‐derived primary macrophages . Interestingly, they found that the knockdown of HMOX1 results in clearance of B. pseudomallei, while the treatment of macrophages with an inducer of HMOX1, CoPPIX, leads to an increased bacterial load.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…HO-1 is a heme-metabolizing enzyme and plays an important role during oxidant-induced injury (50). The role of HO-1 has been found to be responsible for the successful survival of Mycobacterium abscessus (51) and Burkholderia pseudomallei (52). There are reports that HO-1 also facilitates parasite survival of Leishmania sp.…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase-1 production is induced during the course of several infectious diseases as well as inflammatory disorders and may play beneficial or detrimental role for the host depending on the stimulus and context (29, 30, 40, 5157). Mtb infection, in particular, induces a robust production of the enzyme detected in plasma (27, 31, 32) suggesting its potential use as a biomarker for TB.…”
Section: Discussionmentioning
confidence: 99%